The Azores Current System from a meridional section at 24.5ºW - Comas-Rodríguez, Isis; Hernández-Guerra, Alonso; Fraile-Nuez, Eugenio; Martínez-Marrero, Antonio; Benítez-Barrios, Verónica María; Pérez-Hernández, María Dolores; Vélez-Belchí, Pedro (Journal of Geophysical Research, 2011)
High spatial resolution hydrographic data, including Lowered Acoustic Doppler Current Profiler (LADCP) measurements, were acquired along a meridional section at 24.5°W in October 2009. The data are analyzed in detail with the purpose of definitively defining and quantifying the zonal Azores Current System. The Azores Current and Azores Countercurrent are delimited, each extending meridionally for 110 km. The Azores Current is located between 33.5°N and 34.5°N, flanked to the north by the Azores Countercurrent (35.25°–36.25°N). Vertically, both currents reach the γn = 27.975 kg m−3 level (∼2000 m depth), their mass transports ranging across thermocline as well as intermediate layers. The Azores Current transports 13.9 Sv (1 Sv = 106 m3 s−1 ≈ 109 kg s−1) eastward with its maximum associated with the Azores Front (33.75°N). The Azores Countercurrent flows below the surface, transporting 5.5 Sv westward. This contributes to a net eastward flow of 8.4 Sv across the section. At intermediate layers, the Azores Countercurrent transports mixed Mediterranean Water to the west, and the Azores Current transports mixed Sub-Arctic Intermediate Water to the east. Shipboard ADCP and satellite-derived geostrophic velocity are used to confirm the transports revealed by the hydrographic data. Sí